STUDIES ON PREVALENCE OF TRYPANOSOME INFECTION IN ABATTOIRS IN ASABA, DELTA STATE, NIGERIA - Chibuogwu, Francisca U.; Ajunwa, Linda O.; Oyo, A. Ekpo; Preye, Tarela M.; Ebulue, Rose O.; Achagwa, S. Musa; Onyeagu, Chika L.; Enoh, Emmanuel; Ofikwu, Paula O.; Jonah, Alice O. (FUDMA JOURNAL OF SCIENCES, 2023)
This study investigated the prevalence of trypanosome infection in cattle and Red Sokoto (R.S) goats slaughtered at abattoirs in Asaba, Delta State.  304 animals comprising 265 cattle, 39 R.S goats were examined. Blood was collected from the jugular vein of each animal into EDTA containers, placed in cold boxes and transported to the Nigerian Institute for Trypanosomiasis Research (NITR) laboratory in Asaba where standard trypanosome detection methods (STDM), Haematocrit centrifugation technique (HCT) and Buffy coat methods were used to detect trypanosomes and determine Packed Cell Volume (PCV). The result of the investigation showed that seventeen (17) animals were infected giving an overall prevalence of 5.59%. Fifteen (5.66%) of the cattle and two (5.13%) of the R.S goats were infected. Female cattle had higher prevalence of trypanosomiasis (6.78%) than the male cattle (4.76%). Difference in prevalence in female and male cattle was statistically significant (p
Keywords: Prevalence; Trypanosome; Infection